Pemanfaatan Biji Kelor (Moringa oleifera L.) Sebagai Pasta Gigi - Supriadi, Supriadi; Nuryanti, Siti; Maâ€™ruf, Ahmad (Jurnal Akademika Kimia, 2016)
Moringa seed (moringa oleifera L.) is a kind foodstuffs that contains calcium. Calcium is a mineral that is needed by our bodies in all ages, for the infants to the elderly. Calcium is useful in the formation and maintenance of bones and teeth. The aim of this study is to determine the concentration calcium (Ca) in moringa seed (moringa oleifera L.) and its utilization as the fabrication of toothpaste. The method used in this study was a laboratory experiment using a flame photometer. The results showed that the concentration of calcium in moringa seeds with three repetitions was 131.67 Â± 12.58 mg/100g. The appropriate composition of materials to make toothpaste from moringa seeds including the roughness tests of toothpaste and based on the fondness of panelists was 25:5 (morinanga seed:NaHCO3). Furthermore, the test of freshness, aroma, and colour with comparison of glycerin, mint leaves, betel leaves and food coloring 7.5: 5: 5: 2.